2005
DOI: 10.1021/ja053074p
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Xenon Binding Inside the Hydrophobic Cavity of Pseudo-Wild-type Bacteriophage T4 Lysozyme Explored through Xenon-Based NMR Spectroscopy

Abstract: Wild-type bacteriophage T4 lysozyme contains a hydrophobic cavity with binding properties that have been extensively studied by X-ray crystallography and NMR. In the present study, the monitoring of 1H chemical shift variations under xenon pressure enables the determination of the noble gas binding constant (K = 60.2 M(-1)). Although the interaction site is highly localized, dipolar cross-relaxation effects between laser-polarized xenon and nearby protons (SPINOE) are rather poor. This is explained by the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…The L99A cavity in T4 lysozyme is, in many respects, the prototypical nonpolar cavity in proteins. It was one of the first such cavities to be engineered (16) and has been the subject of thermodynamic, structural (16), ligand-binding (17)(18)(19), NMR (20)(21)(22), pressure-dependent, and theoretical studies (23,24). With a volume of Ϸ120 Å 3 , it is larger than one typically obtains from a ''large-to-small'' substitution (e.g., Leu 3 Ala or Phe 3 Ala) in the core of a protein (16,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L99A cavity in T4 lysozyme is, in many respects, the prototypical nonpolar cavity in proteins. It was one of the first such cavities to be engineered (16) and has been the subject of thermodynamic, structural (16), ligand-binding (17)(18)(19), NMR (20)(21)(22), pressure-dependent, and theoretical studies (23,24). With a volume of Ϸ120 Å 3 , it is larger than one typically obtains from a ''large-to-small'' substitution (e.g., Leu 3 Ala or Phe 3 Ala) in the core of a protein (16,25).…”
Section: Resultsmentioning
confidence: 99%
“…It might be noted that, under pressure, this cavity will bind xenon, which has a volume of 45.3 Å 3 (19). There is no evidence that a major change in conformation is required to allow the ligand to reach the binding site (22). Halle and coworkers (30)(31)(32) have also shown that exchange of water at internal sites in proteins is rapid.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this effect enhances NMR sensitivity for the detection of protons in solution [122, 125]. SPINOE was used primarily to study organic molecules containing xenon-accessible cavities such as α-cyclodextrin and cryptophane-A [123] as well as in the context of proteins larger than 100 amino acids [126]. The hydrophobic cavity of the 10 kDa protein β-cryptogein was studied by SPINOE at 1.6 mM in the presence of 5.2 mM ~15% hyperpolarized xenon.…”
Section: Optical Pumpingmentioning
confidence: 99%
“…[3,4] These solutions have had appeal through the emergence of new application fields, [5][6][7] but their direct extension to all liquid-state NMR techniques might be less straightforward than anticipated. Indeed, whatever the magnetic field, the nuclear magnetization of a solution containing 50 mmol L À1 of 129 Xe polarized at 30 % is identical to that of bulk water in a 11.7 T magnet at room temperature.…”
Section: Introductionmentioning
confidence: 99%